Nasal carriage of methicilliin resistant staphylococcus aureus in livestock and farmworkers in Two Communities in Lagos, Nigeria (2019)
The epidemiology of methicillin resistant Staphylococcus aureus (MRSA) is dynamic and thè associated public health risk is likely to increase in settings where there is dose interaction between humans and animals.This study assessed thè occurrence of antimicrobial resistance among S. aureus from livestock and farm personnel, and estimated methicillin-resistance among thè isolates.Two hundred and fifty (250) nasal specimens were collected ffom sheep, goats, cows and farm personnel who had contact with thè animals in two farms in a sub- urban region within Lagos State. Antibiotic susceptibility test was performed using disk diffusion method. The presence of mecA and mecC gene was determined by PCR. S. aureus was recovered from 141 (56.4%) of thè 250 nasal samples analyzed: 32 (22.7%) from cows, 25 (17.7%) from sheep, 32 (22.7%) from pigs, 24 (17.0%) from goats and 28 (19.9 %) from farm workers. Ten isolates, consisting of 4 from cows (8%), 3 from pigs (6%), and 3 from farm personnel (6%), were positive for MRSA. The human-MRSA were recovered from pig workers (2) and a cow farm worker (1). All MRSA strains were resistant to at least three different antimicrobial categories. The MSSA strains were dassified into thirteen antibiotypes of various subtypes. mecC- MRSA was not detected. The high frequency of S. aureus with phenotypic multidrug resistance traits encountered in this study presents a major public health issue. Thus, practices directed at minimizing thè burden of antimicrobial resistance in farm animals should be initiated.